5 years ago, the ratio of a father's and his son's ages was 3:1.
15 years from now, the ratio will be 2:1.
What is the father's current age?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
As there are some claims of alternate answers, it should be noted when the equations from this solution are graphed ( f = 3 s − 1 0 and f = 2 s + 1 5 ) they intersect at only one point, so there is only one possible solution.
Is it not a 20 year passing of time from when they were 3:1 to 2:1 ie 5 years ago and 15 years in the future. Therefore at 3:1 Dad = 60 and Son = 20, 20 years later Dad = 80 years and Son = 40 years 2:1??
Log in to reply
Don't worry reread question - asking for current age not future age
35 30/3=10 35+15=50; 10+15=25 ratio= 2:1 So 35 is also correct.
Log in to reply
Note that it is "15 years from now", and not "15 years from then (5 years ago)".
The father is 60 now son is 30. 15 years ago they were 45 & 15 respectively. 65 may be algebra correct but cannot be true. That makes son 32.5 now and 17.5 15 years before. 3 x 17.5 is 52.5. Therefore 65 is incorrect.
Log in to reply
Note that it is "5 years ago" and not "15 years ago".
Dad past......30 and son 10.....3 times 10 years later the Dad is 40 and the son is 20 ......2 times older...so assumption between past and present is mid way! So the dad is 35 and the son is 15!
Log in to reply
Note that it is "15 years from now", and not "15 years from then (5 years ago)".
Let
F
be the present age of the father and
S
be the present age of the son
5 years ago:
S − 5 F − 5 = 1 3
Cross-multiplying, we get
F − 5 = 3 ( S − 5 )
Applying the distributive property, we get
F − 5 = 3 S − 1 5
We want to isolate S on one side of the equation, so that we can easily compute for the required in the problem which is F ,
Adding 1 5 to both sides, we get
F + 1 0 = 3 S
Dividing both sides by 3 , we get
S = 3 F + 1 0
after 15 years:
S + 1 5 F + 1 5 = 1 2
Cross multiplying, we get
F + 1 5 = 2 ( S + 1 5 )
Applying the distributive property, we get
F + 1 5 = 2 S + 3 0
We want to isolate S on one side of the equation for easy substitution,
Subtracting 3 0 from both sides, we get
F − 1 5 = 2 S
Dividing both sides by 2 , we get
S = 2 F − 1 5
Equate S=S: Since S in the first equation is equal to the S in the second equation, we equate them
3 F + 1 0 = 2 F − 1 5
Cross multiplying, we get
2 F + 2 0 = 3 F − 4 5
Adding both sides by 4 5 , we get
2 F + 6 5 = 3 F
Subtracting 2 F from both sides, we get
F = 6 5 y e a r s o l d
Excuse my naivety, but the process you used to go simplify the initial equations into the two boxed equations. How is this done and what are the rules for it? How do we get JUST 'S' on the left and 'F' moved to the right?
Log in to reply
Which step are you not clear with? Are you talking about the step from F + 1 0 = 3 S to S = 3 F + 1 0 ?
this solution is kind of impressive it makes me understand better
The difference between the two data points is 20 years.
Father's current age = f
( 2 f + 1 5 ) − ( 3 f − 5 ) = 2 0
Turning both fractions into their own respective equivalent fractions with a common denominator.
( 6 3 f + 4 5 ) − ( 6 2 f − 1 0 ) = 2 0
Multiply by 6.
( 3 f + 4 5 ) − ( 2 f − 1 0 ) = 1 2 0
Simplify.
f + 5 5 = 1 2 0
Subtract 55.
f = 6 5
For an explanation of the opening expression, we can verify that ( 2 f + 1 5 ) − ( 3 f − 5 ) = 2 0 by virtue of the son also ageing 20 years over the same time ( s + 1 5 ) − ( s − 5 ) = 2 0
If
s + 1 5 f + 1 5 = 2
then
2 f + 1 5 = s + 1 5
And if
s − 5 f − 5 = 3
then
3 f − 5 = s − 5
So
( 2 f + 1 5 ) − ( 3 f − 5 ) = ( s + 1 5 ) − ( s − 5 ) = 2 0
Wow, this is very nice and clean solution!
It's great that you went a step further prove that the solution you've found does indeed satisfy all the conditions. Nicely done!
Log in to reply
I know it's been a while, but it's never too late to say thank you!
This could probably have been the first comment I ever got on Brilliant (I've not been here that long).
I've seen a bit of your activity Pi Han, and I'd like to say that you are a positive influence on the community - Complimentary, willing to like & share problems that you got wrong, and graceful in your own errors. Keep it up!
Log in to reply
Log in to reply
Log in to reply
Log in to reply
@Pi Han Goh – Did you add the exclamation mark? :)
The age of 45 years of the father now also works. Please check on that answer.
Log in to reply
To satisfy both statements with your answer: If the father's current age is 45, then when he was 40 (5 years ago), the son would have been 13 + 1/3 years old (40/3). And when the father is 60 (15 years from now), the son will be 30 (60/2).
When the father aged 20 years, the son will have aged 16 + 2/3 years, which is not possible. The answer cannot be 45.
I would like to see your working to have established 45 as an answer.
Log in to reply
Thank you, I understand completely now. My working out was a bit problematic.
The father's present age is x and son's y
5 years ago ( x − 5 ) : ( y − 5 ) = 3 : 1
, y − 5 x − 5 = 1 3
⇒ x − 5 = 3 y − 1 5
⇒ x − 3 y = 5 − 1 5
⇒ x − 3 y = − 1 0 . . . . . . . . . . . . . . . . . . . . . . . . . . . ( 1 )
Now, 1 5 years from now ( x + 1 5 ) : ( y + 1 5 ) = 2 : 1
⇒ y + 1 5 x + 1 5 = 1 2
⇒ x + 1 5 = 2 y + 1 5 = 2 y + 3 0
⇒ x + 2 y = 3 0 − 1 5
⇒ x − 2 y = 1 5 . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . ( 2 )
From equation (1) and (2) ,
x - 3y = - 10
x- 2y = 15
(-) (+) (-)
− y = − 2 5
y = 2 5
Now, father's age
⇒ x − 2 × 2 5 = 1 5
⇒ x = 1 5 + 5 0
x = 6 5
Therefore , father's Present age is 6 5
Doesn't say how old in the first place 15 right
what is the word "guess" in the first line of your solution . . .
The father is 3x times older than his son 5 years ago and after 20 years total the father is 2x times older than his son so we can do this ecuation:
3x + x = 2x + x + 20
3x + x = 3x + 20
X= 20
So the son must be 20 years and the father 60 years 5 years ago. Then now they are 25 years old and 65 years old. And after 15 years they are 40 and 80 so that means the awnser is correct.
You have made some little spelling mistakes in your solution. It's equation instead of 'ecuation' and it's answer instead of 'awnser'
suppose, 5 years ago, fathers age was x and sons age was y.
so,the ratio was x/y =3/1
or, x =3y..............................(1)
again, 15 years from now fathers age will be x=(x+20) and sons age will be y=(y+20)
so,the ratio will be , x+20 /y+ 20 = 2/1
or, x=2y +20.....................(2)
now, 3y = 2y +20..........................(x=x)
or, y=20
so, the current age of father is= x+5= 3 x 20 +5=65........................[using equation 1]
Please don't use "X times older than you" as equivalent to "X times as old as you". They don't mean the same thing.
Problem Loading...
Note Loading...
Set Loading...
f − 5 = 3 ( s − 5 ) ⇒ f = 3 s − 1 0
f + 1 5 = 2 ( s + 1 5 ) ⇒ f = 2 s + 1 5
3 s − 1 0 = 2 s + 1 5 ⇒ s = 2 5 ⇒ f = 6 5
The father is 6 5 years old now.